A newsreel history of the Third Reich: Volume 04 [videorecording (DVD)] : 1940 : part two. (Artsmagic, 2006)
"Includes unique footage plundered by Russian Troops in 1945. Compiled as it is from German newsreels which were made under the influence of Goebbels' ministry of propaganda, these are by no means accurate histories but allow unique insight into how the period leading up to and including WW2 was presented to the German people. Volume 4 deals with the second part of the year 1940. It covers the planning of 'Operation Sea-Lion' (the invasion of Great Britain); Great Britain's retaliatory bombing strikes on Berlin; The postponement of 'Operation Sea-Lion' for the invasion of North Africa and the Mediterranean; Mussolini's fa[s]cist Italy's attacks on Greece and Egypt."--Container.